Extension of historical range of Betylobraconinae (Hymenoptera: Braconidae) into Palaearctic Region based on a Baltic amber fossil, and description of a new species of Mesocentrus Szépligeti from Papua New Guinea - Butcher, Buntika Areekul; Zaldivar-Riverón, Alejandro; Kamp, Thomas Van De; Rolo, Tomy Dos Santos; Baumbach, Tilo; Quicke, Donald L. J. (Zootaxa, 2014)
Two new species of the parasitic wasp genus Mesocentrus Szépligeti (Betylobraconinae) are described. One based on a new species from Papua New Guinea, the other the first Palaearctic member of the subfamily based on a 30+ mya, species from Baltic amber. The second species is illustrated using synchrotron X-ray microtomography. Whereas the extant Betylobraconinae are restricted to Australia, New Guinea and New Caledonia, their ancestral distribution is now known to have extended considerably further. A key to the four species of Mesocentrus known from Papua New Guinea is provided. Both species possess some putatively plesiomorphic characters absent in other extant Mesocentrus spp. The new extant species differs in having a considerably larger number of antennal segments and a less laterally depressed frons, while the extinct one has the clypeus separated from the face dorsally and strongly developed hypoclypeal depression. Availability of sequence data for this species enabled further analysis of the relationships of the subfamily, which we present in a phylogenetic analysis additionally including the release of a number of new sequences of related taxa.